The Study of Cotton Extraction by Using Microwave Assisted - Kusumattaqiin, Fataa; Fitriyana, Fitriyana; Halim, Abdul; Mismawati, Andi (ALKIMIA, 2020)
This work aimed to learn the effect of concentration, temperature, and time of extraction toward physical appearances and also changes in lattice parameters. The failed extraction was exhibited by black, transparent, and undissolved cotton. Meanwhile, successful products were indicated by the white suspension. This research was carried out by using the microwave-assisted machine to extract the cotton. The optimum conditions were reached at 55% acid concentration, 30°C reaction temperature, varied time reaction from 1 to 15 minutes. The refinement by using Rietica’s software and Le Bail’s method showed that the extraction product in a monoclinic crystal structure. It was found the compatibility between experimental data and calculation results. The refinement references were a = 0.82 nm, b = 1.03 nm, c = 0.78 nm, α = γ = 90 º and β = 84. Lattice parameter after hydrolysis was greatly different with cotton, mainly in a.